Insights into the Activities and Usefulness of Deoxynojirimycin and Morus alba: A Comprehensive Review - Angela Fulvia Tricase; Maria Maddalena Cavalluzzi; Alessia Catalano; Michela De Bellis; Annalisa De Palma; Giovanna Basile; Maria Stefania Sinicropi; Giovanni Lentini (Molecules)
Deoxynojirimycin (DNJ), the first isolated iminosugar, is a natural alkaloid acting as a potent inhibitor of α-glucosidase with high nutritional value. It naturally occurs in plants (especially Morus spp.), microbes, and insects or can be synthesized. Diverse biological activities, such as antihyperglycemic, lipid-lowering, antitumor, antiviral, and anti-inflammatory, have been recognized for this compound. However, DNJ has not been approved as a food supplement until now. Several studies, also in clinics, are carried out on Morus spp. containing DNJ. Among Morus spp., Morus alba L. (white mulberry), Morus nigra L. (black mulberry), and Morus rubra L. (red mulberry) are the three main species that grow all over the world. Some spurious studies have been conducted on Reducose® and Glubloc™, two products that contain DNJ and Morus alba, respectively. However, mulberry allergy, including respiratory allergy, airborne contact urticaria, anaphylaxis, oral allergy syndrome, and food induced urticaria, may be observed. This review aims to explore a crucial and timely question: how DNJ exerts its biological effects and what role it may play in therapeutic applications. We provide a comprehensive summary of the current understanding of DNJ’s pharmacological potential and the methods used for its production. We also report recent developments in clinical studies on Morus alba, Reducose® and Glubloc™.